Letter - Cwmamman Trades and Labour Council, 11 May 1926 (Cwmamman)
1926-05-11 "Letter - Cwmamman Trades and Labour Council, 11 May 1926" [g0150001.jpg], 11 May 1926, Cwmamman Trades and Labour Council Local Organisation